Cultural Quarters as a Means of Enhancing the Creative Capacity of Polish Cities? Some Evidence from Cracow - Murzyn-Kupisz, Monika (Quaestiones Geographicae, 2012)
Culture-oriented activities conducted by diverse actors in selected urban areas may lead to the formation of unique quarters of production and consumption of cultural goods and services which function both as creative hubs and leisure spaces. Such cultural quarters may develop spontaneously or as a result of official designation and major public investment. Referring to the debate on cultural quarters in Western Europe, this article aims to examine the issue of the spatial concentration of cultural and creative activities within a selected large city in Poland. The author analyses recent transformations of two historic quarters in Cracow (Kazimierz and Podgórze) and considers the extent to which both areas can be regarded as successful cultural quarters. She describes their emergence and the changes observed in them in terms of groupings, character and number of creative-sector firms established there, pondering whether their role is limited to a function as centres of commercial cultural entertainment and night-life consumption, or whether they indeed stimulate the development of a creative economy.